MIXING UP THE TYPES OF CLASSROOM INTERACTION USED IN YOUR ESL CLASS (Conferencea, 2023)
The article gives the information about the teacher activeness in class.Different types of classroom interaction you can use to vary your lesson plan, the teacher simply in the role of facilitator.